Association of the veterans aging cohort study index with exercise capacity in HIV-infected adults. - Oursler, Krisann K; Tate, Janet P; Gill, Thomas M; Crothers, Kristina; Brown, Todd T; Crystal, Stephen; Womack, Julie; Leaf, David A; Sorkin, John D; Justice, Amy C (AIDS research and human retroviruses, 2013)
Physical disability is a major priority in aging, affecting morbidity, mortality, and quality of life. Despite the large number of adults aging with HIV, our understanding of the physiologic and clinical risk factors for disability is limited. Our goal is to determine whether the Veterans Aging Cohort Study (VACS) Index, based on routine clinical blood tests, could serve as a point of care screening tool to identify HIV-infected adults at high risk for physical disability. HIV-infected adults enrolled in the VACS participated in a cross-sectional exercise study with established measures of strength and endurance. The VACS Index was calculated using recent clinical laboratory values and age; a higher score reflects greater mortality risk. Statistical analyses included correlation and linear regression models adjusted for muscle mass. Fifty-five HIV-infected adults, predominantly African-American men, were included with age mean±SD of 52±7 years. Median (IQR) CD4 cell count was 356 cells/mm(3) (212-527). The VACS Index was inversely correlated with quadriceps strength (r=-0.45, p<0.01), grip strength (r=-0.28, p=0.04), and 6-min walk distance (r=-0.27, p=0.05). A 20-point increase in VACS Index score was associated with a 10% lower leg strength (p<0.01), which remained significant after adjustment for muscle cross-sectional area (p=0.02). The VACS Index explained 31% of the variance in specific leg strength. In this group of middle-aged adults with well-controlled HIV infection the VACS Index was significantly associated with upper and lower extremity strength. The VACS Index may be valuable for identification of patients at high risk for disability due to muscle weakness.
Keywords: Adult; Aging; Biological Markers; Body Composition; CD4 Lymphocyte Count; Cohort Studies; Cross-Sectional Studies; Exercise; Female; HIV Infections; Humans; Male; Middle Aged; Muscle Strength; Physical Endurance; Risk Factors